Journalistic Practice: Constructive Journalism - Hooffacker, Gabriele. author. aut Link
VIII, 47 p. 1 illus.
Keywords: Adolescents want media that report in an understandable way and show backgrounds and possible solutions. This book shows how the concept of constructive journalism helps with this and how it can be used in journalism training. This springer essential is a translation of the original German 1st edition essentials, Journalistische Praxis: Konstruktiver Journalismus by Gabriele Hooffacker, published by Springer Fachmedien Wiesbaden GmbH, part of Springer Nature in 2020. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors. The contents Using constructive journalism in crisis reporting · Producing media for adolescents · Using scenarios and video material for journalism education The target groups Journalists in studies and training, in editorial offices and in public relations · Teachers at universities, academies and journalism schools · The author Gabriele Hooffacker (*1959), Dr. phil., is a Professor teaching at the Faculty of Computer Science and Media at Leipzig University of Applied Sciences. She publishes the textbook series "Journalistic Practice” (Journalistische Praxis) at Springer VS. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.